Evaluation of Smoking Cessation Advice in a Maltese Mental Health Community Clinic - N. Cortis; A. Pace; G. Grech (European Psychiatry, 2022)
Introduction Tobacco smoking is one of the leading causes of preventable morbidity and mortality worldwide (WHO, 2020). Smoking cessation campaigns have been effective at reducing smoking in the general population, but not in individuals with mental illness (Lê Cook et al., 2014). A downward trend in smoking has been noted in EU countries but smoking rates have remained stable in Malta (Country Health Profile, 2019).